Pengaruh Metode Pembelajaran Problem Solving Terhadap Kreativitas Belajar Matematika Siswa Pada Materi Pecahan Di Kelas V SD Negeri Karing-Karing - Suwarni La Usa; Komang Resky Pratiwi (Jurnal Akademik Pendidikan Matematika, 2021)
The formulation of the problem in this study is whether the Problem Solving learning method has an effect on students' creativity in learning mathematics on fractions material in class V SD Negeri Karing-Karing?. The population in this study is all fifth grade students of SD Negeri Karing-Karing in the academic year 2021/2022, totaling 36 students consisting of 2 classes which are also used as samples using saturated sampling technique. The data collection of this study used a description test, and analyzed using the Independent-Samples T Test analysis. The results of this study showed that based on the results of descriptive analysis, the average value of increasing creativity in learning mathematics for experimental class students was 82.37; the average increase in students' mathematics learning creativity in the control class was 72.37. And based on the results of inferential analysis by using the t-test, it is known to be significant at 0.014 0.05, which means that H0 is accepted. So it can be concluded that there is an effect of the Problem Solving learning method on the creativity of students' mathematics learning in the fraction material in class V SD Negeri Karing-Karing